2020
DOI: 10.1186/s12964-020-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs12982687 affects binding capacity of lncRNA UCA1 with miR-873-5p: involvement in smoking-triggered colorectal cancer progression

Abstract: Background: This investigation was arranged to elucidate whether single nucleotide polymorphisms (SNPs) of lncRNA UCA1 was implicated in elevating colorectal cancer (CRC) risk by interacting with environmental exposures.Methods: LncRNASNP database was firstly adopted to predict SNPs that possibly affected binding of UCA1 with miRNAs and then the interactive effect of SNPs and environmental exposure on CRC risk was evaluated by recurring to type 2 gene-environment interactions (GEI) model. Besides, MTT assay, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Another example was described for colorectal cancer, when SNP rs12982687 in the lncRNA UCA1 intervened in the binding capacity of UCA1 with different miRNAs, especially miR-873-5p. 56 Also, a similar process occurs in HOTAIR, where the rs2366152C variant has the potential to gain a new binding site for miR-22 in cervical cancer. 57 The interaction of lncRNAs with one or more biomolecules such as DNA, RNA or other proteins has already been described.…”
Section: One Of the Most Successful Gwas Results Highlights That Mostmentioning
confidence: 92%
See 1 more Smart Citation
“…Another example was described for colorectal cancer, when SNP rs12982687 in the lncRNA UCA1 intervened in the binding capacity of UCA1 with different miRNAs, especially miR-873-5p. 56 Also, a similar process occurs in HOTAIR, where the rs2366152C variant has the potential to gain a new binding site for miR-22 in cervical cancer. 57 The interaction of lncRNAs with one or more biomolecules such as DNA, RNA or other proteins has already been described.…”
Section: One Of the Most Successful Gwas Results Highlights That Mostmentioning
confidence: 92%
“…A single nucleotide alteration in a lncRNA target inside a miRNA binding site sequence can block the interaction with lncRNA‐miRNA and modulate the process in a cell tumor. Another example was described for colorectal cancer, when SNP rs12982687 in the lncRNA UCA1 intervened in the binding capacity of UCA1 with different miRNAs, especially miR‐873‐5p 56 . Also, a similar process occurs in HOTAIR, where the rs2366152C variant has the potential to gain a new binding site for miR‐22 in cervical cancer 57 …”
Section: Discussionmentioning
confidence: 98%
“… 30 In our results, the G allele of rs6695584 was associated with poorer overall survival than the A allele, suggesting that the genotype of this risk loci might serve as a predictor of the clinical outcome of CRC patients. Analogously, Fu et al 31 demonstrated that CRC patients with genotypes TT/CT of rs12982687 enjoyed a more favorable prognosis than those with homozygote C. Genetic background combined with molecular biomarkers and clinical features could construct a more accurate model for the outcome of CRC patients.…”
Section: Discussionmentioning
confidence: 95%
“…For example, tea polyphenols (TPs) can exert anti-inflammatory, anti-oxidant, or pro-oxidant effects to promote apoptosis and act at multiple levels to inhibit CRC growth and metastasis (233). Nicotine upregulates the expression of UCA1 and HIF-1a in CRC cells and promotes the proliferation and metastasis of CRC cells (234). In addition, individuals with a family history of colorectal cancer and inflammatory bowel disease are more likely to develop colorectal cancer than individuals without such a family history of these diseases (4).…”
Section: Discussionmentioning
confidence: 99%